2011
DOI: 10.1159/000327022
|View full text |Cite
|
Sign up to set email alerts
|

Childhood-Adolescent Obesity in the Cardiorenal Syndrome: Lessons from Animal Models

Abstract: Background/Aims: Childhood-adolescent overweight and obesity have grown to pandemic proportions during the past decade. The onset of obesity in younger adults will likely be manifested as earlier onset of myocardial and renal end-organ disease in younger adults. For the first time, it is estimated that the current generation may not live to be as old as their parents. Thus, it is important to develop animal models of childhood obesity to understand fundamental pathological organ changes. Methods: In this regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…It is suggested that the renal reduction in oxidative stress and proinflammatory cytokines is very likely to be related to the prevention of subsequent podocyte injury and fibrosis. A possible link between adipose tissue and renal damages as suggested in childhood-adolescent obesity 52 deserves further investigation in the beneficial influence of dietary sodium restriction in fructose-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the renal reduction in oxidative stress and proinflammatory cytokines is very likely to be related to the prevention of subsequent podocyte injury and fibrosis. A possible link between adipose tissue and renal damages as suggested in childhood-adolescent obesity 52 deserves further investigation in the beneficial influence of dietary sodium restriction in fructose-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Islet fibrosis is related to systemic (cRAAS) and islet RAAS (tRAAS) ( Section 2 ), islet redox stress and RONS ( Section 3 ) and systemic and islet inflammation ( Section 4 ). Islet fibrosis is a common finding early on in MetS and T2DM, which is found not only in preclinical animal models ( Figure 8 ) but also in adult humans ( Figure 9 ) [ 20 , 22 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. The pancreatic stellate cell is important [ 48 , 50 ] and may reflect the activation of the peri-islet pericytes in the Ren2 model of lean hypertension with excess renin and Ang II ( Figure 8 ).…”
Section: Islet Fibrosismentioning
confidence: 99%
“…These abnormalities precede the development of albuminuria and glomerular injury and animals show a parallel deterioration in cardiac output and renal function ( 89 ). Ultrastructural studies have shown cardiomyopathy in both the OZ rat, and in mice with a similar mutation (db/db mouse) ( 90 ). A comprehensive analysis in the db/db mouse has shown that albuminuria/glomerulopathy and cardiac contractile dysfunction appear after 2–4 months of hyperglycemia ( 91 ).…”
Section: Cardiac and Renal Involvement In Systemic Disease (Type 5 Crmentioning
confidence: 99%